THE ROLE OF ISLAMIC BUSINESS ETHICS IN THE DEVELOPMENT OF MICRO, SMALL, AND MEDIUM ENTERPRISES (MSMES) - M. Guffar Harahap; Cita Ayni Putri Silalahi (INTERNATIONAL, Journal of Sharia Business Management, 2025)
This research aims to analyze the role of Islamic business ethics in the development of Micro, Small, and Medium Enterprises (MSMEs). This study uses a mixed approach with a quantitative method in the form of a survey of MSMEs and a qualitative method in the form of an in-depth interview with MSME owners or managers. The results of the study show that Islamic business ethics have a positive and significant influence on the performance of MSMEs. The honesty dimension is the key factor that has the most influence on the performance of MSMEs. MSMEs that apply Islamic business ethics at a high level have better performance compared to MSMEs that apply Islamic business ethics at a low level. The implementation of Islamic business ethics in MSMEs still faces several challenges, such as lack of understanding, lack of resources, and unfair competition. This research provides implications for MSME actors, the government, Islamic financial institutions, and subsequent researchers.